THU0133 Results from A Phase 2A, Randomized, Multicenter, Double-Blind, Placebo-Controlled, Parallel-Group Study of Jnj-40346527, an Oral CSF-1R Inhibitor, in Patients with Active Rheumatoid Arthritis despite Disease-Modifying Antirheumatic Drug Therapy. (10th June 2014) - Genovese, M.C.; Hsia, E.; Belkowski, S.; Chien, C.; Masterson, T.; Thurmond, R.; Manthey, C.; Yan, D.; Ge, T.; Greenspan, A.
Abstract : Background: JNJ-40346527, an investigational agent, is a selective inhibitor of the colony stimulating factor-1 receptor (CSF-1R) kinase and acts to inhibit macrophage survival, proliferation and differentiation. Based on current understanding of their mechanisms of action, JNJ-40346527 and traditional DMARDS may have complementary effects in reducing inflammation in rheumatoid arthritis (RA). Objectives: To assess the safety, tolerability, and efficacy of JNJ-40346527 compared with placebo (PBO) administered for 12wks to patients with active RA despite DMARD therapy. Methods: In this randomized, double-blind, PBO-controlled, parallel-group study, adult RA patients were randomized (2:1) to receive JNJ-40346527 100mg or PBO twice daily. RA patients had active disease (persistent disease activity with ≥6 swollen/6 tender joints at screening and baseline and a CRP level ≥0.8mg/dL at screening) despite MTX, SSZ, and/or HCQ therapy at the time of screening. Patients had to be on MTX, SSZ, and/or HCQ therapy for ≥6 months prior to screening, with a stable dose for minimum of 8wks prior to screening; patients were to continue stable DMARD therapy through wk12. Primary endpoint was change from baseline in DAS28 (CRP) at wk12. Efficacy analyses were based on m-ITT, defined as all randomized patients who had received ≥1 study agent administration and who had a baseline and at least one post-baseline value. Pharmacokinetics (PK) and pharmacodynamics assessments were performed. Conclusions: Despite evidence of adequate PK exposure and effective peripheral target engagement, no consistent evidence of efficacy was observed in the JNJ-40346527 group vs PBO in patients with active RA despite DMARD therapy. No statistically significant difference was observed between the groups in any of the efficacy parameters analyzed; treatment was generally well-tolerated. Disclosure of Interest: : M. Genovese Grant/research support: Janssen Research & Development, LLC, E. Hsia Employee of: Janssen Research & Development, LLC, S. Belkowski Employee of: Janssen Research & Development, LLC, C. Chien Employee of: Janssen Research & Development, LLC, T. Masterson Employee of: Janssen Research & Development, LLC, R. Thurmond Employee of: Janssen Research & Development, LLC, C. Manthey Employee of: Janssen Research & Development, LLC, D. Yan Employee of: Janssen Research & Development, LLC, T. Ge Employee of: Janssen Research & Development, LLC, A. Greenspan Employee of: Janssen Research & Development, LLC DOI: 10.1136/annrheumdis-2014-eular.2404